2013
DOI: 10.1016/j.ecolecon.2012.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction and air quality in Europe

Abstract: Concerns for environmental quality and its impact on people's welfare are fundamental arguments for the adoption of environmental legislation in most countries. In this paper, we analyse the relationship between air quality and subjective well-being in Europe. We use a unique dataset that merges three waves of the European Social Survey with a new dataset on environmental quality including SO 2 concentrations and climate in Europe at the regional level. We find a robust negative impact of SO 2 concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
161
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(179 citation statements)
references
References 35 publications
11
161
0
Order By: Relevance
“…In the past, studies on air pollution and wellbeing generally suggested that poor air quality is a significant and negative predictor of wellbeing (e.g., Levinson, 2012;Welsch, 2002Welsch, , 2006Welsch, , 2007Welsch, , 2009Zeidner & Shechter, 1988). Self-reported life satisfaction (e.g., Ferreira et al, 2013;Li et al, 2014;Liao et al, 2014;Luechinger, 2009Luechinger, , 2010MacKerron & Mourato, 2009;Rehdanz & Maddison, 2008;Welsch, 2006) and positive and negative emotions (e.g., Bullinger, 1989;Yeatts et al, 2014;Zeidner & Shechter, 1988), which are three elements of SWB, were measured as the main indicators of wellbeing in these studies. In other words, the view that air pollution has a negative effect on hedonic wellbeing has been corroborated repeatedly.…”
Section: Theoretical and Practical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, studies on air pollution and wellbeing generally suggested that poor air quality is a significant and negative predictor of wellbeing (e.g., Levinson, 2012;Welsch, 2002Welsch, , 2006Welsch, , 2007Welsch, , 2009Zeidner & Shechter, 1988). Self-reported life satisfaction (e.g., Ferreira et al, 2013;Li et al, 2014;Liao et al, 2014;Luechinger, 2009Luechinger, , 2010MacKerron & Mourato, 2009;Rehdanz & Maddison, 2008;Welsch, 2006) and positive and negative emotions (e.g., Bullinger, 1989;Yeatts et al, 2014;Zeidner & Shechter, 1988), which are three elements of SWB, were measured as the main indicators of wellbeing in these studies. In other words, the view that air pollution has a negative effect on hedonic wellbeing has been corroborated repeatedly.…”
Section: Theoretical and Practical Contributionsmentioning
confidence: 99%
“…This means people who were living in Beijing breathed healthy air on only 56% of the days of the year. On the one hand, the growing air pollution will definitely interfere with a better life for people; on the other hand, the rising GDP, indicators of wellbeing used were usually life satisfaction (e.g., Ferreira et al, 2013;Li, Folmer, & Xue, 2014;Liao, Shaw, & Lin, 2014;Luechinger, 2009Luechinger, , 2010MacKerron & Mourato, 2009;Welsch, 2006;Rehdanz & Maddison, 2008), and the presence of positive mood and the absence of negative mood (e.g., Bullinger, 1989;Cuñado & de Gracia, 2013;Yeatts, Cready, Pei, Shen, & Luo, 2014;Zeidner & Shechter, 1988), which are basic components of SWB (Diener, Suh, & Oishi, 1997;Lucas, Diener, & Suh, 1996).…”
mentioning
confidence: 99%
“…These requirements, however, are typically met in practice. 10 So far, the life satisfaction approach has been applied to a variety of contexts (see, for example, Welsch (2002Welsch ( , 2006Welsch ( , 2007, Rehdanz and Maddison (2008), Menz (2011), Ferreira et al (2013), or Ambrey et al (2014 for the context of air pollution; Israel and Levinson (2003) for the context of water pollution; Frijters and van Praag (1998), Rehdanz and Maddison (2005), and Maddison and Rehdanz (2011) Specifically, the studies which are most closely related to this study are van Praag and Baarsma (2005) and Rehdanz and Maddison (2008) for the context of noise pollution and Ambrey and Fleming (2011) and Kopmann and Rehdanz (2013) Kopmann and Rehdanz (2013) find that the willingness to pay for artificial land covers, such as minding, dumping, and construction sites, is negative.…”
Section: Life Satisfaction Approachmentioning
confidence: 99%
“…5 As the life satisfaction approach has already been applied to valuing other environmental externalities monetarily, including air pollution (see, for example, Welsch (2002Welsch ( , 2006Welsch ( , 2007, Rehdanz and Maddison (2008), Ambrey and Fleming (2011), Menz (2011), Ferreira et al (2013), Kopmann and Rehdanz (2013), or Ambrey et al (2014)) or noise pollution (see, for example, van Praag and Baarsma (2005) or Rehdanz and Maddison (2008)), we contribute to a steadily growing stream of literature.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of methods of measuring judgments about feelings, "satisfaction with life", used by the World Values Survey (World Values Survey 2016), and "the Cantril Ladder" by Gallup, Inc. (Gallup 2016), are well known. With respect to policy proposal contributions, advantages of this approach have been demonstrated in various ways, including an investigation of the relationship between atmospheric pollution and a decline in subjective well-being (Ferreira et al 2013). However, no studies have quantitatively evaluated the effects of environmental countermeasures, such as radiation-related countermeasures, on anxiety and well-being.…”
Section: Introductionmentioning
confidence: 99%